Do Maternal Self-Criticism and Symptoms of Postpartum Depression and Anxiety Mediate the Effect of History of Depression and Anxiety Symptoms on Mother-Infant Bonding? Parallel–Serial Mediation Models - Beato, Ana Filipa; Albuquerque, Sara; Kömürcü Akik, Burcu; Costa, Leonor Pereira da; Salvador, Ágata (Frontiers in Psychology, 2022)
Introduction History of depression symptoms, including before and during pregnancy, has been identified as an important risk factor for postpartum depression (PPD) symptoms. This condition has also been associated with diverse implications, namely, on the quality of mother–infant bonding. Moreover, the role of self-criticism on PPD has been recently found in several studies. However, the link between these factors has not been explored yet. Furthermore, anxiety symptoms in postpartum has been less studied. Methods This study analyzed whether the history of depression symptoms predicted mother–infant bonding, via self-criticism and PPD symptoms. The same model was repeated with a history of anxiety and postpartum anxiety symptoms. A total of 550 mothers of infants <24 months old participated in this cross-sectional study and answered an online survey. Results Through a parallel–serial mediation model, the results show that in a first step, self-criticism dimensions of inadequate-self, hated-self, and reassuring-self, and in a second step, PPD symptoms, mediate the relationship between the history of depression symptoms and mother–infant bonding. However, the relationship between the history of anxiety symptoms and bonding is not mediated by all the considered chain of mediators, being only mediated by one of the self-criticism dimensions, inadequate self. Conclusions The current study confirmed the association of history of both depression and anxiety with mother–infant bonding. While in the case of history of anxiety symptoms, the relation was only mediated by inadequate self-dimension of self-criticism, in the case of history of depression symptoms, the relation was mediated by self-criticism and postpartum depressive symptoms. The buffering effect of reassuring-self on bonding and negative affect was also evidenced. Psychological and preventive interventions should address this evidence to target interventions for mother–infant bonding problems in accordance with previous and actual current maternal risk factors.